Pengaruh Aplikasi Al-Qur`an Digital terhadap Motivasi Beribadah Mahasiswa Purwakarta - Nabilah, Khairun; Fajrussalam, Hisny; Ilahi, Anisa Mutiara; Fauziah, Dhea Resti; Amelia, Shela (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
When man has a high motivation to worship God, then man is worshipped and full of enthusiasm. The Digital Qurâ€™an is an application that contains the Qurâ€™an in gadgets. However, as the interest of Students in using gadgets in everyday life and downloading digital Qurâ€™an apps increases, on the other hand, the app is just as a decoration. For that, the author conducted a study with the title â€œThe Impact of the Digital Qurâ€™an Application on the Motivation of Students in Purwakartaâ€. Research was conducted to find out whether the application of the digital Qurâ€™an influenced the motivation of student worship in Purwakarta. In this study, the researchers used a quantitative method, using the â€œSelf-Administered Questionnairesâ€ technique. The study population was Students in Purwakarta with a total of 20 Students. The data collection technique used is through a questionnaire. The data analysis technique used is a simple regression test. The results of this study show that the application of the Digital Qurâ€™an has an impact on the motivation of students to worship in Purwakarta. On the linear regression result that is derived from the data analysis of significance values on the positive question variable that shows the value of Thitung > Table (3,257 > 2,10092), the data indicates that there is an influence and significance between the application of the Digital Qurâ€™an to the student motivation in Purwakarta. Keywords: Purwakarta students, motivation for worship, application of the digital Qurâ€™an